The Impact of Adaptive Learning in Entrepreneurial Behavior for College Students - Yang, Dan (Frontiers in Psychology, 2022)
Entrepreneurship of college students has always been a hot topic in families, schools and society. Massive studies aim to explore entrepreneurial behavior. However, under the condition of the 10% success rate of student entrepreneurship, the adverse impact of COVID-19 and the changed circumstance of domestic entrepreneurship, this exploration aims to study the factors that influence college students’ entrepreneurial behavior choices under the epidemic. First, through the retrieval of relevant literature and theoretical study, the variable factors that affect behavior choices are sorted and summarized. It is assumed that the factors that affect behavior choices are entrepreneurial motivation, entrepreneurial ability, willingness to behave, and entrepreneurial environment. Second, a questionnaire is designed to investigate the choice of entrepreneurial behavior for students who are starting a business or going to start a business. The standard effect values of the survey results are calculated by using structural equation modeling (SEM). The results reveal that the effect values of the nine hypothetical results are all in line with the prediction, which prove a positive impact of the four variable factors on the choice of entrepreneurial behavior. The experimental parameters set are as follows. The standardized effect value of Hypothesis 1 (entrepreneurial motivation has a positive impact on entrepreneurial behavior choice) is 0.216; that of Hypothesis 2 (entrepreneurial ability has a positive impact on the choice of entrepreneurial behavior) is 0.221; that of Hypothesis 3 (willingness to behave has a positive impact on entrepreneurial behavior choice) is 0.284; that of Hypothesis 4 (entrepreneurial environment has a positive impact on the choice of entrepreneurial behavior) is 0.329; that of Hypothesis 5 (entrepreneurial motivation has a positive impact on entrepreneurial intention) is 0.247; that of Hypothesis 6 (entrepreneurial ability has a positive impact on willingness to behave) is 0.339; that of Hypothesis 7 (entrepreneurial ability has a positive impact on entrepreneurial motivation) is 0.357; that of Hypothesis 8 (entrepreneurial environment has a positive impact on willingness to behave) is 0.336; that of Hypothesis 9 (entrepreneurial environment has a positive impact on entrepreneurial motivation) is 0.485. Besides, the entrepreneurial environment has the greatest impact on behavior choice. Therefore, it is believed that the government, society, schools need to strengthen the correct guidance of entrepreneurial students and create a good entrepreneurial environment to cope with economic changes under the epidemic.